2013
DOI: 10.1080/19315260.2013.837134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postharvest Handling Practices on Physicochemical Composition of Tomato

Abstract: Tomato (Solanum lycopersicum L.) is the most commercially produced and widely used vegetable. The physiological nature of tomato makes it vulnerable to quality deterioration during postharvest handling along the supply chain. Effects of postharvest handling practices on qualitative changes in cvs. Onyx and Rio Grande were evaluated along the supply chain. Fruit samples were collected at harvest, during transport, and at marketing. Cultivar affected physicochemical composition of tomato. In the period from harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
4
1
Order By: Relevance
“…There was a negative correlation between ash levels and moisture (-0.63*). Osack & Monica (2013) and Ferreira et al (2010), working with table tomato found ash content ranging between 0.24 g 100 g -1 to 0.37 g 100 g -1 , values lower than those obtained in the present work. The physical and chemical fruit characteristics presented vary according to the genetic factor, place of cultivation, cultivation management, harvest season, stage of maturity, among others (Santos et al, 2010).…”
Section: Biometrical and Physicochemical Characteristicscontrasting
confidence: 91%
“…There was a negative correlation between ash levels and moisture (-0.63*). Osack & Monica (2013) and Ferreira et al (2010), working with table tomato found ash content ranging between 0.24 g 100 g -1 to 0.37 g 100 g -1 , values lower than those obtained in the present work. The physical and chemical fruit characteristics presented vary according to the genetic factor, place of cultivation, cultivation management, harvest season, stage of maturity, among others (Santos et al, 2010).…”
Section: Biometrical and Physicochemical Characteristicscontrasting
confidence: 91%
“…These results also corresponded with findings of Tigist and coworkers whom reported that higher loss of titratable acids during storage could be related to higher respiration rate as ripening advances where organic acids are used as a substrate in respiration process (Tigist, Workneh, & Woldetsadik, 2013). Similar finding was reported by Isack and Monica; acidity is often used as an indication of maturity as acid decreases during ripening of fruit (Isack & Monica, 2013). On the other hand, no significant effects in soluble solid content, pH and ascorbic acid content were observed in all the treatments (Table 2).…”
Section: Postharvest Quality Studysupporting
confidence: 91%
“…Tomato (Solanum lycopersicum L.) belongs to the family Solanaceae is one of the most popular and worldwide consumed vegetable crops. It is also the most processed vegetable crop and ranks rst in commercial and nutritional contribution to the human diet (Dandena et al, 2013;Isack and Monica, 2013;Asfaw and Eshetu, 2015;Ankit et al, 2016;Mawardii et al, 2017).…”
Section: Introductionmentioning
confidence: 99%